Effect of Imbrasia belina meal on growth performance, quality characteristics and sensory attributes of broiler chicken meat. Issue 1 (11th November 2020) - Moyo, Sipho; Masika, Patrick Julius; Muchenje, Voster; Jaja, Ishmael Festus
Abstract: The study aimed to evaluate the effect of dietary graded levels of Imbrasia belina at 0%, 4%, 8% and 12% of broiler diets on meat quality and sensory attributes. A total of 360 one-day-old broiler chicks, were fed graded I. belina diets and slaughtered on day 35. Body weight (BW), Average Daily Gain (ADG), Feed Intake (FI) and Feed Conversion Ratio (FCR) were recorded. Breast muscles were evaluated for ultimate pH, meat colour (L* (lightness), a*(redness), b*(yellowness), tenderness, cooking loss. Forty consumer panellists evaluated sensory attributes. On day 28, the ADG in birds fed IB4 (88.06 g) and control (80.09 g) were statistically similar. On day 28 and 35 FI of broiler chickens fed control (147.47 g; 178.45 g) was the highest. The highest values for L* were observed in IB1, but not significantly different ( p  > .05) from IB3 and IB4. For redness, a* values were highest in IB3 and lowest in IB1. Lightness, yellowness, pH24 and Hue showed a quadratic response to increasing levels of IB meal. The shear force values were highest in IB1 (11.27), but not significantly different ( p  > .05) from IB3 (9.97) and IB4 (9.85). However, the tenderness scores were observed to be highest from IB3 (7.00). The highest acceptability scores of the breast meat were from IB2 (7.65). In conclusion, adding graded levels of I. belina meal up to 12% into diets of broilers had a positive effect on growth performance, meat quality and sensory attributes. Highlights: Dietary inclusion levels of I. belina meal increased body weight gains in dietary treatment groups. The shear force in all dietary treatment groups decreased compared to the control. The tenderness of breast meat was found to be significantly influenced by the dietary treatment